The Role of Interactive e-Modules Based on Realistic Mathematics Education to Improve Mathematical Representation Ability - Annisa, Dewi; Khairunnisak, Cut; Fadhiliani, Dwi; Zubaidah, Tuti (Universitas Teknokrat Indonesia, 2025)
Excellent mathematical representation ability is needed by students to develop and deepen understanding and relationships between mathematical concepts. Therefore, the teacher has the responsibility to create learning that encourages mathematical representation ability. The existence of interactive e-modules with a realistic mathematic education approach makes it easy for students to learn interactively and adapt to different students' mathematical abilities. This study aims to determine the improvement of mathematical representation ability from the use of interactive e-modules with realistic mathematics education approach. This research is a quantitative research conducted on seventh grade students of SMPN 18 Banda Aceh which is divided into experimental and control classes. The data analysis technique used was analysis of variance (ANOVA) followed by t-test. The results showed that students' mathematical representation ability in the experimental class was better than the control class. The interaction between the use of E-modules and students' initial mathematical ability on mathematical representation ability showed that the use of E-modules and early mathematical ability together had a significant effect on improving mathematical representation ability. Students who have high early math ability have a great influence if given treatment in the form of using RME-based e-modules. Students with low early mathematical ability did not experience significant improvement. Interactive e-modules with the RME approach can be used to improve mathematical representation skills by considering students' early mathematical abilities.